ANALISIS YURIDIS TERHADAP MUNCULNYA SERTIPIKAT HAK MILIK ATAS TANAH PERKEBUNAN KELAPA SAWIT PERORANGAN ATAS KEKUATAN SURAT KEPALA DESA TANPA DIKETAHUI PEMILIKNYA (STUDI PUTUSAN PTUN NOMOR : 08/G/2011/PTUN MDN)” - PAULUS PAULUS (PREMISE LAW JURNAL, 2016)
The procedure of issuing ownership certificate of plantation and individual land stipulated in the Directive of the Head of BPN No. 4/1998 on the Guidelines forgiving and Canceling State Land Right and the Government Regulation No. 24/1961. By the help of the Village Head, SIM (Tilling License) is issued on land-reform after the requirement for tilling period is fulfilled. Itis then transferred to the applicant who registers in P2T section of the Land Office toget the certificate. There are two kinds of land certificate: free State land in which the documents are Identity Cards and written notification and non-free State Land in which the documents are renunciation of rights, property title, and location layout. Legal consequence of the position of ownership certificate of individual oil palm plantation in the Ruling of PTUN No. 08/G/2011/PTUN-MDN, although there is the double Letter of Notifications made by the Village Head, the Land Certificate cannot be cancelled because it has met the requirement for the registration, and its legal basis of the purchasing contract is the Letter of Notification which has been issued before the legal basis owned by the plaintiff. Keywords: Plantation Land, Land Registration, Double Letter of Notification from Village Head